Agrobacterium tumefaciens-MEDIATED IN-PLANTA TRANSFORMATION OF INDONESIAN MAIZE USING pIG121Hm-Cs PLASMID CONTAINING nptII AND hpt GENES - Edy Listanto; Eny Ida Riyanti; Sustiprijatno Sustiprijatno (Indonesian Agency for Agricultural Research and Development, 2016)
Maize (Zea mays L.) productivity in Indonesia is challenged to be increased using genetic engineering. Recent advances in Agrobacterium tumefaciens-mediated in-planta transforma-tion makes it possible to transform maize with low cost, and simple method. This study aimed to confirm pIG121Hm-Cs plasmid in A. tumefaciens, and to estimate the efficiency level of A. tumefaciens-mediated in-planta transformation of Indonesian maize by using pIG121Hm-Cs plasmid containing nptII and hpt genes. A series of studies were conducted including confirmation of gene construct of pIG121Hm-Cs plasmid in A. tumefaciens, transformation of four maize lines through A. tumefaciens-mediated in-planta technique, acclimatization of transformant plants and molecular analysis of selected plants using polymerase chain reaction (PCR). The pIG121Hm-Cs plasmid was confirmed via PCR analysis using specific primers of nptII and hpt genes and resulted 700 bp and 500 bp for fragments of nptII and hpt, respectively. After selection, acclimatization and molecular analysis steps, the efficiency levels of transformation of four maize lines were low, ranging from 3.8% to 12.8%. The level of transformation efficiency of ST-27 line was the highest accounting for 12.8% of 45 planted embryos on selection medium based on PCR analysis using specific primer for nptII gene. Overall, A. tumefaciens-mediated in planta transformation on maize floral pistil in this study proved to be successful and rapid. Therefore, this enhanced transformation method will be beneficial for Indonesian maize genetic engineering.